Predictive Value of TRIB3 Combined with BMPR2 for Major Adverse Cardiovascular Events in Elderly Coronary Heart Disease Patients Undergoing Percutaneous Coronary Intervention: Clinical significance of BMPR2 and TRIB3 in coronary artery disease - Zhang, Qiang; Dong, Aiqiao; Wang, Tian; Kang, Fei; Wang, Huan; Sun, Jing (Journal of Medical Biochemistry, 2025)
Background: This research aims to explore the correlation of Tribbles Pseudokinase 3 (TRIB3) and bone morphogenetic protein receptor type 2 (BMPR2) with coronary heart disease (CHD), as well as the evaluation value of the combined detection of the two for major adverse cardiovascular events (MACE) following percutaneous coronary intervention (PCI). Methods: The study enrolled 152 CHD patients (CHD group) who underwent PCI treatment between January 2023 and May 2024 and 136 healthy individuals (control group) who concurrently underwent physical examination in our hospital. The expressions of TRIB3 and BMPR2 in the serum of both groups were measured. The clinical implications of these two factors in CHD, along with their diagnostic value for CHD, were then analyzed. Subsequently, the CHD patients were subjected to a 6-month follow-up. During this period, the occurrence of MACE was recorded and the evaluation value of the combined detection of TRIB3 and BMPR2 for MACE was analyzed.Results: In the CHD group, the concentration of TRIB3 was significantly elevated compared to the control group, existing a notable decline in TRIB3 levels after treatment (P
Keywords: oronary heart disease; major adverse cardiovascular events; BMPR2; TRIB3; percutaneous coronary intervention